2021
DOI: 10.1016/j.neuroimage.2021.118165
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Decoding of Spatial and Color Processing in Human Prefrontal Cortex

Abstract: The prefrontal cortex (PFC) plays a pivotal role in goal-directed cognition, yet its representational code remains an open problem with decoding techniques ineffective in disentangling task-relevant variables from PFC. Here we applied regularized linear discriminant analysis to human scalp EEG data and were able to distinguish a mental-rotation task versus a color-perception task with 87% decoding accuracy. Dorsal and ventral areas in lateral PFC provided the dominant features dissociating the two tasks. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…One possible explanation could be the differential processing of colors in distinct brain regions or pathways, which could account for this timing disparity. Additionally, the literature supports the notion that the choice of color may influence EEG decoding accuracy in color-perception tasks, as seen in a study using red and green-colored stimuli where it is reported that the beta-band provided the highest EEG decoding accuracy of color-perception tasks vs. mental-rotation tasks 77 while using red and green-colored stimuli. Moreover, the observation of faster beta frequency responses to red and blue colors compared to green may be indicative of differences in alertness.…”
Section: Discussionsupporting
confidence: 53%
“…One possible explanation could be the differential processing of colors in distinct brain regions or pathways, which could account for this timing disparity. Additionally, the literature supports the notion that the choice of color may influence EEG decoding accuracy in color-perception tasks, as seen in a study using red and green-colored stimuli where it is reported that the beta-band provided the highest EEG decoding accuracy of color-perception tasks vs. mental-rotation tasks 77 while using red and green-colored stimuli. Moreover, the observation of faster beta frequency responses to red and blue colors compared to green may be indicative of differences in alertness.…”
Section: Discussionsupporting
confidence: 53%
“…Goldman-Rakic and others applied this methodology to the study of WM by manipulating the spatial locations of task stimuli; their results confirmed and extended earlier findings supporting PFC as a critical node for WM because they found that some PFC neurons’ activity was not just elevated during the delay, but elevated in a manner specific to the spatial location of the remembered stimulus ( Funahashi et al, 1989 ). Follow-up studies extended findings that PFC activity not only represents spatial stimulus features, but also other non-spatial stimulus features like motion direction ( Zaksas and Pasternak, 2006 ), object ( Wilson et al, 1993 ), prospective code ( Rainer et al, 1999 ), abstract rules ( Wallis et al, 2001 ), categories ( Freedman et al, 2001 ), color ( Min et al, 2021 ), etc. Additionally, this spatially-selective delay activity was later found to extend beyond neurons in the PFC and into other high-order regions related to attentional control, including the posterior parietal cortex ( Chafee and Goldman-Rakic, 1998 ), leading to a view of WM as centered in the PFC, with related representations in high-order regions of the parietal cortex with which the PFC is strongly interconnected.…”
Section: Neuroanatomy Of Wmmentioning
confidence: 66%
“…Recent neuroimaging techniques have been able to objectively measure the contribution of PFC involvement in human activity (Parris et al, 2019 ; Udina et al, 2019 ; Min et al, 2021 ). Traditional brain imaging techniques such as functional magnetic resonance imaging (fMRI) has a high spatial resolution to detect cerebral blood flow signals.…”
Section: Introductionmentioning
confidence: 99%